2023
DOI: 10.3390/pharma2020012
|View full text |Cite
|
Sign up to set email alerts
|

Cost Estimations of Managing Adverse Drug Reactions in Hospitalized Patients: A Systematic Review of Study Methods and Their Influences

Abstract: This study aimed to systematically review and explore the impact of study methods on the cost of managing adverse drug reactions (ADRs) among hospitalized patients to guide policymakers and researchers. A literature search was conducted in MEDLINE, EMBASE, CINAHL, Cochrane Library, and Google Scholar. The search was restricted to studies from 2000 to 2017. Two authors independently reviewed the studies, assessed their risk of bias, and extracted information for analysis. Data abstraction was based on the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The median increase in LOS for these episodes was 4 days (2–7 days) [ 3 ]. A recent systematic review revealed that, in high-income countries, the average cost per ADR case ranged from USD 2908.7 to USD 12,129.9, and in low-income countries, from USD 65.0 to USD 581.7 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The median increase in LOS for these episodes was 4 days (2–7 days) [ 3 ]. A recent systematic review revealed that, in high-income countries, the average cost per ADR case ranged from USD 2908.7 to USD 12,129.9, and in low-income countries, from USD 65.0 to USD 581.7 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taking this context into account, pharmacovigilance 7 is understood as one of the clinical services that make up pharmaceutical care 8 and is aimed at practicing actions to promote the identification, evaluation, resolution, and prevention of adverse drug-related events (Figure 1). In addition, through pharmacovigilance, studies are carried out to gain a better understanding of ADRs, as well as reporting these cases to each country's surveillance system, which is also known as phase IV of medication development or postmarketing surveillance 7 . In Brazil, around 12,000 notifications are made every year by national risk management services involving the practice of pharmacovigilance 9 .…”
mentioning
confidence: 99%